FACTORS AFFECTING MUZAKKI'S INTEREST IN DISTRIBUTING TRADE ZAKAT THROUGH BAZNAS - Ali Hardana; Lismawati Hasibuan; Jafar Nasution; Arti Damisa; Aliman Syahuri Zein; Sry Lestari (FEBI Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
BAZNAS has the goal of alleviating poverty and creating an attitude of independence for mustahik, so community empowerment through the distribution of aid funds carried out by BAZNAS is increasingly being developed. Mustahik can create things that are beneficial to the surrounding environment and have the potential to become muzakki. The initial income from trade zakat funds in 2018 in North Padang Lawas was Rp. 100,000,000 while what was collected in 2019 was Rp. 17,000,000 from these data it can be concluded that there is a lack of community in giving trade zakat. This research is a quantitative research, the data source used is primary data and data collection using questionnaires and interviews. The research sample was 30 samples using saturated sampling technique, then the research analysis used statistics, namely SPSS Version 20. The results of the study based on the t test show that the religiosity variable (X1) has an effect on muzakki's interest in channeling trade zakat funds while the trust variable (X2) and promotion variable (X3) have no effect on muzakki's interest in channeling trade zakat funds. Then based on the results of the F test it is known that the variables of religiosity, trust, and promotion have an effect on muzakki's interest in channeling trade zakat funds at Baznas Padang Lawas Utara.